DOP66 Disease course of Ulcerative proctitis in children: A population based study on behalf of the SIGENP IBD Group. (21st January 2022) - Martinelli, M; Fedele, F; Romano, C; Aloi, M; Lionetti, P; Alvisi, P; Panceri, R; Bramuzzo, M; Illiceto, M; Bosa, L; Norsa, L; Pastore, M; et al.
Abstract: Background: Ulcerative proctitis (UP), defined as a colonic location limited to the rectum, is a poorly investigated condition in children, usually considered as a minor form of Ulcerative Colitis (UC). The aim of the present study was to compare the disease course of paediatric patients affected by UP at diagnosis with the other UC locations. Methods: This multicentre retrospective observational study has been carried out starting from the data prospectively registered in the IBD Registry of the Italian Society of Pediatric Gastroenterology, Hepatology and Nutrition (SIGENP). Seventeen IBD referral centres adhering to the registry were included in the study. Patients age 0 to 18 years, who were diagnosed with UC according to the Porto criteria starting from January 1, 2009, to May 1st, 2021 were identified. Only children with a minimum follow-up of 12 months were included in the study. Once enrolled, children were subsequently divided in two groups based on Paris classification: group 1 (E1) and group 2 (E2, E3 and E4). Results: Eight-hundred-eighty-five children were finally included in the study (median age at diagnosis: 11.2 years, range: 0–18 years; M/F: 434/451), of whom 176 (19.8%) belonging to group 1 and 709 (80.1%) to group 2. The median age at diagnosis was significantly higher in group 1 when compared to group 2 [11.9 (0–18) versus 11 (0–18) years, respectively; (p<0.001)]. At diagnosis, the induction therapy was significantly different with 68 (39.5%) patients of group 1 undergoing steroid therapy versus 505 (71.2%) of group 2 (p<0.001) and 79 (41.9%) of group 1 practising only mesalamine respect to 186 (26.2%) of group 2 (p<0.001). A higher number of children from group 2 started immunosuppressive or biologic therapy as maintenance therapy at diagnosis [Group 1: 11 (6.2%) versus 173 (24.4%), respectively; (p<0.001)]. The median follow-up of our cohort was 4.5 years (range 1–13 years). At the last follow-up, 67/176 (38%) children with UP showed an extension of their disease location without significant difference when compared to group 2 [265 (37.5%); p=0.9], while 81 (45%) children from Group 1 were under immunosuppressive or biologic therapy versus 566 (79.8%) from group 2 (p<0.001). Five children (3%) of Group 1 underwent colectomy during the follow up versus 45 (6.9%) of Group 2 (p=0.06). Conclusion: UP is a frequent location of paediatric onset UC and the risk of endoscopic extension of proctitis is similar to the more extensive forms. A considerable number of patients with UP required immunosuppressive or biologic therapy during the follow-up and no significant difference was observed in terms of surgery. Overall, UP cannot be considered as a minor form of UC.